Pelatihan Digital Marketing dan Pertanian Usaha Berbasis Platform Digital Guna Meningkatkan Jangkauan Pemasaran Produk UMKM di Desa Yosowilangun Lor, Lumajang - Basuki Basuki; Retno Purnama Sari; Vega Kartika Sari; Muhammad Rizal Romadhon (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Based on the identification of problems that occur in UMKM in Yosowilangun Lor Village, there are obstacles to marketing that are still traditional. This activity aims to help MSME problems in product marketing so that MSMEs are more advanced and product sales can increase through digital marketing. The stages of the activity are carried out with socialization, training, and mentoring of MSMEs. The material presented includes the correct procedures for product photos and videos, the use of social media and copywriting, the application of business accounting, and tagging Google maps locations. MSME actors enthusiastically participate in MSME outreach, training and mentoring activities. So that this shows that MSME actors provide a positive attitude and have high interest and curiosity in participating in the activities that have been carried out